2019
DOI: 10.19055/ams.2019.10/28/3
|View full text |Cite
|
Sign up to set email alerts
|

Discovering factors influencing study success of students with disabilities and learning difficulties in an interview study

Abstract: The focus of our research is on students with disabilities defined by the current National Higher Education Act in Hungary. The actuality of the topic is that after the millennium, due to the expansion of higher education, the above-mentioned students appeared at universities, but regulations dealing with their presence in Hungary were laid down as late as 2007. Earlier researches have studied the accessibility and inclusive practices of the institutions internationally and in Hungary, but only little attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This was expected since we are examining a group for whom learning is problematic for various reasons. We can also see that the socioeconomic background of the families is lower in the group of students with special educational needs, which corresponds to the patterns of the international and Hungarian literature [68,91,92].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This was expected since we are examining a group for whom learning is problematic for various reasons. We can also see that the socioeconomic background of the families is lower in the group of students with special educational needs, which corresponds to the patterns of the international and Hungarian literature [68,91,92].…”
Section: Discussionsupporting
confidence: 72%
“…Research on learners (who do not have special educational needs) highlighted long ago that low parental involvement, the quality of parent-child interactions, family lifestyle and values, and the socioeconomic characteristics of the family have an impact on early school leaving and academic success [62][63][64][65][66]. However, research on students with special educational needs has shown that families of children with special educational needs have lower social status, higher divorce rates, and poorer quantitative and qualitative indicators of parent-child interaction than the general population [67,68]. Research on families raising children with special educational needs has often focused on the lack of family relationships as a negative consequence of raising children who have special educational needs [69,70].…”
Section: Social Capital In Families Of Children With Special Educatio...mentioning
confidence: 99%
See 2 more Smart Citations